Cerebral Ischemia in Active Giant Cell Arteritis: Clinical and Diagnostic Aspects in 36 Patients - Pfadenhauer, K.; Ertl, M.; Hittinger, M.; Berlis, A. (Aktuelle Neurologie, 2016)
Background: Cerebral ischemia (CI) is an uncommon, sometimes life-threatening complication of active giant cell arteritis (aGCA) due to affection of the precerebral arteries.Aim of the Study: To analyze and describe clinical findings and results of multimodal vascular imaging of the craniocervical arteries.Patients and Methods: Out of 317 aGCA patients, 36 (11%) presented with CI. All patients underwent vascular imaging including ultrasonography (US) of the temporal arteries (TA) and precerebral arteries, biopsies were taken in 27, CTA/MRA were performed in 21 and FDG-PET in 18 patients.Results: In 72% of patients, CI was located in the posterior circulation and in14% of patients, it occurred after beginning of steroid therapy. TA were normal on clinical and US examination in 10 patients (with normal biopsies in 5) but PET demonstrated GCA of the precerebral arteries in 9 of them. Abnormalities of the precerebral arteries typical of GCA were demonstrated by US as halos in 67% (in 61% halos of the vertebral arteries), CTA/MRA in 43% and PET in 72% of patients. Concurrent etiologies for CI were evident in 19% of patients (including >50% ICA stenosis in 3 and atrial fibrillation in 4 patients).Conclusions: Awareness for GCA as a cause of CI requiring specific diagnostic and therapeutic steps is important. US, CTA, MRA and PET are valuable diagnostic tools for rapid detection of GCA involving the precerebral arteries in different stages of the disease even if the TA look normal.
Keywords: giant; cell; arteritis; cerebral; ischemia